STRATEGI KOMUNIKASI PEMASARAN DALAM MEMPERTAHANKAN LOYALITA PELANGGAN - Ardini, Nurhaliza Sandra Dwi; Hindra, Nurnawati; Itasari, Andri Astuti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This study aims to find out the marketing communication strategy implemented by Mitra10 Solo Baru Supermarket in maintaining customer loyalty. The research method used in this study is qualitative descriptive, data is collected through in-depth interviews with 3 management of the new Mitra10 Solo Supermarket and 3 loyal customers, as well as direct observation in the company. The theory used to show customer loyalty of Supermaket Mitra10 Solo Baru is a theory of promotion mix stages in the form of advertising, sales promotion, public relations, and personal selling proposed by Kotler (2016). The results of this study show that a planned and directed marketing communication strategy can maintain customer loyalty at Mitra10 Solo Baru Supermarket. The implementation of the promotion mix stage theory is a key factor in creating and maintaining strong relationships with customers. Keywords: Mitra10 Supermarket, marketing communication, promotion mix